Tuber Yield of Radish (Raphanus sativus L.) as Affected by Different Frequencies of Hydroponic Waste Nutrient Solution Application - De Guzman, Ronel S.; Coronel, Justine Gabriel H.; Dumlao, Maybelyn P.; Grimaldo, Reinz E.; Revasto, Joyce Ann C. (Future Science / FSH-PH Publications, 2026)
In this study, the tuber yield of Radish (Raphanus sativus L.) was explored under lahar-laden soil conditions treated with hydroponic waste nutrient solution at a different frequency. The experiment was arranged in a randomized complete block design (RCBD) with 4 treatments and 3 replications at Lahar-laden Technology Demonstration Area, President Ramon Magsaysay State University, San Marcelino Zambales. T1 (no application; control), T2 (once a week), T3 (twice a week) and T4 (thrice a week). Traits such as tuber length, tuber diameter, tuber weight (per plant), and tuber yield (per m2) were measured; means of treatments were then subjected to analysis of variance (ANOVA) followed by mean comparison test with Tukey's Honestly Significant Difference Test. Rank in root tuber yield in all variables brevity of similar treatments had a P ⟨ 0.001 significant effect on root tuber yield. The first rank in maximum tuber length (21.40 cm), tuber diameter (45.03 mm), tuber weight per plant (132.09 g) and yield (6.60 kg/m2) recorded at T4 level remained higher than other treatment units however the difference was found statistically significant up to 0.05% level of significance. T3 the next highest, and control had the lowest. Mean tuber weight per plant and yield (kg/m2) showed an obvious dose-response relationship with significant differences among means between all treatments. Based on the results, the application of hydroponic waste nutrient solution more frequently can significantly improve radish production, and applying hydroponic waste nutrient solution three times a week was the best treatment from this study.